Stereospecificity of Ketoreductase Domains 1 and 2 of the Tylactone Modular Polyketide Synthase - Castonguay, Roselyne (2008)
Tylactone synthase (TYLS) is a modular polyketide synthase that catalyzes the formation of tylactone (1), the parent aglycone precursor of the macrolide antibiotic tylosin. TYLS modules 1 and 2 are responsible for the generation of anti-diketide and triketide intermediates, respectively, each bound to an acyl carrier protein (ACP) domain. Each module harbors a ketoreductase (KR) domain. The stereospecificity of TYLS KR1 and TYLS KR2 has been determined by incubating each of the recombinant ketoreductase domains with reconstituted ketosynthase—acyltransferase [KS][AT] and ACP domains from the 6-deoxyerythronolide B synthase (DEBS) in the presence of the N-acetylcysteamine thioester of syn-(2S,3R)-2-methyl-3-hydroxypentanoate (6), methylmalonyl-CoA, and NADPH resulting in the exclusive formation of the ACP-bound (2R,3R,4S,5R)-2,4-methyl-3,5-dihydroxyhepanoyl triketide, as established by GC-MS analysis of the TMS ether of the derived triketide lactone 7. Both TYLS KR1 and KR2 therefore catalyze the stereospecific reduction of the 2-methyl-3-ketoacyl-ACP substrate from the re-face, with specificity for the reduction of the (2R)-methyl (D) diastereomer. The dehydration that is catalyzed by the dehydratase (DH) domains of TYLS module 2 to give the unsaturated (2E,4S,5R)-2,4-dimethyl-5-hydroxyhept-2-enoyl-ACP2 is therefore a syn elimination of water.